Sleep as the foundation of health: The role of sleep in human life, impact on memory, mood, and physical activity - Klaudia Maria Kufel; Dariusz Paweł Fabian; Karolina Michalczuk; Marek Kurowski; Elżbieta Monika Leszczyńska-Knaga; Natalia Anna Jakubczyk; Weronika Rutkowska-Kawalec; Paweł Krzysztof Moczydłowski; Monika Ryglewicz; Anna Gliwa; Karolina Anna Kuczapska (Quality in Sport)
Sleep is a key component of everyone's health. It plays an important role in the body's recovery, improvement of cognitive function, and overall well-being. This thesis explores various aspects of sleep, focusing on its physiology, functions, and role in daily life. The paper includes detailed analyses of the effects of sleep on memory, the effects of deprivation, and techniques to improve sleep quality, such as sleep duration and regularity, minimising alcohol and caffeine intake, and meditation practices. The link between sleep and physical activity is also proving to be extremely important. Regular activity affects sleep quality and mental health. Finally, sleep is the foundation of health and well-being. Despite the wealth of information we already have, the importance and role of sleep presented in the following article demonstrate that this area should invariably be the subject of further research to help us gain an even better understanding of, and therefore influence, the quality of our sleep.